Reducing Hospital Readmissions in Chronic Obstructive Pulmonary Disease Patients: Current Treatments and Preventive Strategies - Claudia Di Chiara; Giulia Sartori; Alberto Fantin; Nadia Castaldo; Ernesto Crisafulli (Medicina)
COPD is one of the leading causes of death worldwide, so it represents a significant public health challenge. Over the years, new effective therapies have been proposed. However, the burden of COPD is still conditioned by frequent acute events defined as exacerbations (exacerbation of COPD-ECOPD), which have a significant impact not only on the patient’s quality of life but also on the progression of the disease, morbidity, and mortality. Related to the severity of the condition, ECOPD may require hospital admission and often repeatedly more admissions (readmission). The phenomenon of readmissions is a significant problem, contributing substantially to the utilisation of healthcare resources and the economic burden of COPD. Related contributing factors are still poorly understood, and managing the patients readmitted to the hospital with ECOPD may be challenging. Hospital readmissions should be optimally managed, including supporting and preventive strategies. Although early readmissions (30 days from discharge) are a marker of the quality of the patient’s care, we need to consider COPD patients globally. It is not sufficient to address just the acute events, so multidimensional management is necessary, able to follow the patient over time to identify, by a personalised approach, the correct treatment during and post hospitalisation and intercept any factor affecting the natural history of the disease, comprising the risk of hospital readmissions. In the context of the literature concerning respiratory medicine, particularly COPD patients, our narrative review analyses recent evidence regarding the current management of COPD hospital readmissions, aiming to propose preventive strategies helpful in clinical practice. The proposed strategies can potentially improve clinical outcomes and reduce healthcare costs when effectively implemented in practice.